2021
DOI: 10.1021/acs.jafc.1c04216
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Droplet Wetting and Pinning Behaviors on Pathogen-Modified Hydrophobic Surfaces: Strategies and Working Mechanisms

Abstract: Hydrophobic surfaces modified by pathogens in agricultural production are one of the main reasons to reduce the utilization of pesticides. Adding surfactants to pesticide solutions is a common method to improve their wetting and spreading properties. In this work, the interaction mechanism between pathogen-modified hydrophobic surfaces and mixtures of surfactants and a pesticide was studied in detail. The interaction mechanism was determined by characterizing the wetting and spreading behaviors of droplets on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The tendency of the wetting state of the droplet is mainly due to the movement of surfactant molecules and the micellar state in the droplet (Figure C). Our previous studies have shown that as powdery mildew continues to occur, wetting of droplets requires more surfactant molecules or semimicelles to overcome droplet pinning forces . Another function of surfactants is to evenly distribute pesticide particles on the surface of cucumber powdery mildew leaves, especially in the grooves of the powdery mildew layer, which is conducive to pesticide action on the powdery mildew foundation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendency of the wetting state of the droplet is mainly due to the movement of surfactant molecules and the micellar state in the droplet (Figure C). Our previous studies have shown that as powdery mildew continues to occur, wetting of droplets requires more surfactant molecules or semimicelles to overcome droplet pinning forces . Another function of surfactants is to evenly distribute pesticide particles on the surface of cucumber powdery mildew leaves, especially in the grooves of the powdery mildew layer, which is conducive to pesticide action on the powdery mildew foundation.…”
Section: Resultsmentioning
confidence: 99%
“…According to the experimental parameters combined with the model, the pinning force for droplets on the leaves of cucumber powdery mildew at different growth stages ranges from 0.0011 to 0.0643. Overall, the pinning force of the Hexa+Silwet618 droplets is relatively low, indicating that the wetting ability of the Hexa+Silwet618 droplets is strong and not easily affected by the gullies in the powdery mildew layer . The parameters for the droplet wettability were calculated by using a correlation model, which provides a basis for evaluating the wettability and trend for droplets on cucumber powdery mildew leaves at different growth stages.…”
Section: Resultsmentioning
confidence: 99%
“…30 He et al also made a corresponding study on the wetting and pinning behaviors of conditioning droplets on pathogen-modified hydrophobic surfaces as well as the whole process of regulating pesticide application on pathogen-modified hydrophobic leaf surfaces at different growth stages. 38,39 In the pursuit of more effective and sustainable pest management in litchi cultivation, the development of novel pesticides requires careful consideration of specific characteristics. Two key attributes that an ideal novel pesticide should possess are: Target Specificity, the novel pesticide should demonstrate a high degree of specificity, precisely targeting the site of infestation in litchi.…”
Section: Discussionmentioning
confidence: 99%
“…The retention and wetting behavior of liquids is a natural performance, which is common in many industrial and agricultural processes. In the process of controlling crop diseases and insect pests by constant-volume pesticide spray, pesticide diluent is atomized by spraying equipment and then deposited on the surfaces of crop stems, leaves, flowers, and fruits through air transmission, thus allowing pesticides to play a role . Each surface of crops has unique and complex surface characteristics, surface microstructure, apparent surface free energy (SFE), and so on, which will make pesticide droplets interact with them, leading to different wetting and retention performances and affecting the retention on the target surface, such as pepper fruit, cucumber leaf, , and rice leaf …”
Section: Introductionmentioning
confidence: 99%